The Effect of Training and Development, Supervisor Support, and Compensation on Employee Retention during COVID-19 Pandemic on Nurses of X Hospital in Jakarta - Evita Charolina Ginting; Yohana F. Cahya Palupi Meilani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Employee retention is a fundamental thing in the success of a company or organization, including hospitals. This study aims to determine the effect of training and development, supervisor support, and compensation on employee retention of nurses at X Hospital in Jakarta. This study uses a quantitative method with a sample of 150 nurses who have worked for more than 1 year at Hospital X during the pandemic. Data analysis was performed using SmartPLS software version 3.3.9. The results of this study indicate that training and development, supervisor support, as well as compensation have a positive effect on employee retention. Overall, it can be said that training and development, supervisor support, and compensation have a positive impact on employee retention at Hospital X in Jakarta. It is important for hospital management to pay more attention to these factors in order to retain skilled nurses.